Sumoylation in neurodegenerative diseases - Krumova, Petranka; Weishaupt, Jochen H. (Cellular and molecular life sciences, 2013)
The yeast SUMO (small ubiquitin-like modifier) orthologue SMT3 was initially discovered in a genetic suppressors screen for the centromeric protein Mif2 (Meluh and Koshland in Mol Bio Cell 6:793-807, 1). Later, it turned out that the homologous mammalian proteins SUMO1 to SUMO4 are reversible protein modifiers that can form isopeptide bonds with lysine residues of respective target proteins (Mahajan et al. in Cell 88:97-107, 2). This was the discovery of a post-translational modification called sumoylation, which enzymatically resembles ubiquitination. However, very soon it became clear that SUMO attachments served a far more diverse role than ubiquitination. Meanwhile, numerous cellular processes are known to be subject to the impact of SUMO modification, including transcription, protein targeting, protein solubility, apoptosis or activity of various enzymes. In many instances, SUMO proteins create new protein interaction surfaces or block existing interaction domains (Geiss-Friedlander and Melchior in Nat Rev in Mol Cell Biol 8:947-956, 3). For the past few years, sumoylation attracted increasing attention as a versatile regulator of toxic protein properties in neurodegenerative diseases. In this review, we summarize the growing knowledge about the involvement of sumoylation in neurodegeneration, and discuss the underlying molecular principles affected by this multifaceted and intriguing post-translational modification.
Published: 25 September 2012
Gesehen am 17.06.2021